The specter of genocide - (:unkn) unknown (My University, 2003)
This collection of essays by leading international experts offers an up-to-date, comprehensive history and analysis of multiple cases of genocide and genocidal acts, with a focus on the twentieth century. The book contains studies of the Armenian genocide, the victims of Stalinist terror, the Holocaust, and imperial Japan. Several authors explore colonialism and address the fate of the indigenous peoples in Africa, North America, and Australia. As well, there is extensive coverage of the post-1945 period, including the atrocities in the former Yugoslavia, Bali, Cambodia, Ethiopia, Rwanda, East Timor, and Guatemala. The book emphasizes the importance of comparative analysis and theoretical discussion, and it raises new questions about the difficult challenges for modernity constituted by genocide and other mass crimes
Mass murder in historical perspective
Edited by Robert Gellately, Ben Kiernan. - Cambridge, UK ; New York : Cambridge University Press, 2003. - x, 396 p. ; 24 cm. - Includes bibliographical references and index
Տվյալները՝ ինտերնետային կայքից
https://www.pdfdrive.com/the-specter-of-genocide-mass-murder-in-historical-perspective-d159377709.html
Contents: The mass murder and genocide / Robert Gellately and Ben Kiernan-Pt. I. Genocide and modernity. Twentieth century genocides: underlying ideological themes from Armenia to East Timor / Ben Kiernan-The modernity of genocides: war, race, and revolution in the twentieth century / Eric D. Weitz-Seeking the roots of modern genocide: on the macro-and microhistory of mass murder / Omer Bartov-Genocide and the body politic in the time of modernity / Marie Fleming. Pt. II. Indigenous peoples and colonial issues. Genocides of indigenous peoples: rhetoric of human rights / Elazar Barkan-Military culture and the production of "final solutions" in the colonies: the example of Wilhelminian Germany / Isabel V. Hull-"Encirclement and annihilation": the Indonesian occupation of East Timor / John G. Taylor. Pt. III. The era of the two World Wars. Under cover of war: the Armenian genocide in the context of total war / Jay Winter-The mechanism of a mass crime: the great terror in the Soviet Union, 1937-1938 / Nicolas Werth-The Third Reich, the Holocaust and visions of serial genocide / Robert Gellately-Reflections on modern Japanese history in the context of the concept of genocide / Gavan McCormack. Pt. IV. Genocide and mass murder since 1945. "When the world turned to chaos": 1965 and its aftermath in Bali, Indonesia / Leslie Dwyer and Degung Santikarma-Genocide in Cambodia and Ethiopia / Edward Kissi-Modern genocide in Rwanda: ideology, revolution, war, and mass murder in an African state / Robert Melson-History, motive, law, intent: combining historical and legal methods in understanding Guatemala's 1981-1983 genocide / Greg Grandin-Analysis of a mass crime: ethnic cleansing in the former Yugoslavia, 1991-1999 / Jacques Semelin-Conclusions. Investigating genocide / Robert Gellately and Ben Kiernan-Appendix. Convention on the Prevention and Punishment of the Crime of Genocide
Keywords: Genocide-Crimes against humanity